Thomas Hörl - Curtain walls & Rautenballett - Egger, Simone 1979-; Felderer, Brigitte (Verlag für moderne Kunst, 2022)
Thomas Hörl’s entire oeuvre is pervaded ecstatically with lozenges as pictorial symbols. As a recurring shape, it plays an indispensable role in his performances, installations, drawings, and collages. Patterns emerge from regular and irregular grid-like lines, which condense and dissolve once again. Whether on fabric or paper, on 210 wooden panels, in different sizes, painted, printed, sewn, or glued, individually or in a structure: this characteristic shape is continuously taken up and interpreted. Thomas Hörl combines approaches from many fields and, as an artist, surveys the cultural memory of specific landscapes for fragments for his performative installations. An ethnographic sampling—the recourse to historical bodies of knowledge and remixing local forms of enactment—which, like practices of superstition, eludes a normed determinacy, often forms the departure point for his engagement with the world
Auflage: 555. - Vorzugsausgabe: 55, signiert, nummeriert, Archivdruck, Rautenpuzzle
Keywords: Hörl, Thomas -- 1975-; Collage; Installation -- Kunst; Performance -- Künste; Simone Egger; Thomas Hörl